Fidelity of the Methylation Pattern and Its Variation in the Genome - Ushijima, Toshikazu; Watanabe, Naoko; Okochi, Eriko; Kaneda, Atsushi; Sugimura, Takashi; Miyamoto, Kazuaki (Genome Research, 2003)
The methylated or unmethylated status of a CpG site is copied faithfully from parental DNA to daughter DNA, and functions as a cellular memory. However, no information is available for the fidelity of methylation pattern in unmethylated CpG islands (CGIs) or its variation in the genome. Here, we determined the methylation status of each CpG site on each DNA molecule obtained from clonal populations of normal human mammary epithelial cells. Methylation pattern error rates (MPERs) were calculated based upon the deviation from the methylation patterns that should be obtained if the cells had 100% fidelity in replicating the methylation pattern. Unmethylated CGIs in the promoter regions of five genes showed MPERs of 0.018–0.032 errors/site/21.6 generations, and the fidelity of methylation pattern was calculated as 99.85%–99.92%/site/generation. In contrast, unmethylated CGIs outside the promoter regions showed MPERs more than twice as high (P < 0.01). Methylated regions, including a CGI in theMAGE-A3 promoter and DMR of the H19 gene, showed much lower MPERs than unmethylated CGIs. These showed that errors in methylation pattern were mainly due to de novo methylations in unmethylated regions. The differential MPERs even among unmethylated CGIs indicated that a promoter-specific protection mechanism(s) from de novo methylation was present.[Supplemental material is available online at www.genome.org.]